Robustness in combinatorial optimization and scheduling theory: An annotated bibliography - Yury V. Nikulin (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2004)
This short annotated bibliography focuses on what has been published during the last ten years in the area of combinatorial optimization and scheduling theory concerning robustness and other similar techniques that deal with worst case optimization under uncertainty and non-accuracy of problem data.
Keywords: 650; robustness; tolerance; worst-case scenario; input data uncertainty; non-accuracy; flexibility of solution; maximal regret; Scheduling-Verfahren; Robustes Verfahren; Theorie